Exploring the Interfacial Phase and π–π Stacking in Aligned Carbon Nanotube/Polyimide Nanocomposites - Qian Jiang; Qian Zhang; Xianyan Wu; Liwei Wu; Jia-Horng Lin (Nanomaterials, 2020)
To characterize the interfacial microstructure and interaction at a nanoscale has a significant meaning for the interface improvement of the nanocomposites. In this study, the interfacial microstructure and features of aligned multiwalled carbon nanotube (MWNT) and conjugated polymer polyimide (PI) with three molecular structures were investigated using small-angle X-ray scattering (SAXS), wide-angle X-ray diffraction (WAXD), and fluorescence emission spectroscopy. It was found that aligned MWNT/PI nanocomposites had a nonideal two-phase system with the interfaces belonging to long period stacking ordered structure. Attributed to the π–π stacking effect, MWNT/BTDA-MPD presented the most regular arrangement verified by fractal dimension. By adopting a one-dimension correlation function, each phase dimension in aligned MWNT/PI nanocomposites was calculated and verified by high resolution transmission electron microscopy (HRTEM) and X-ray diffraction (XRD). The π–π stacking was demonstrated to be an important interaction between MWNT and PI via WAXD and fluorescence emission spectroscopy, and it was influenced by the linkage bond between benzene rings in PIs. This work is of significance to reveal the interfacial features between conjugated polymer and carbon nanotubes (CNTs), which is favorable for the interface design of CNT-based high performance nanocomposites.